Strategi Industrialisasi Hubungan dengan Sektor Lain pada Pembangunan - Devrianti Rahma Satria; Moch. Reza Ivaldianto; Muhammad Yasin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Industrialization has been a major driver in Indonesia’s transition from an agrarian to a modern economy. Its contribution to productivity growth, job creation, and economic diversification makes it a strategic component of national development. The integration between industry and other sectors such as agriculture, services, trade, and labor proves essential in strengthening competitiveness and achieving inclusive growth. Findings indicate that despite its potential, industrialization in Indonesia still faces challenges such as import dependency, limited skilled labor, and regional disparities. Therefore, future industrial strategies should focus on enhancing sectoral linkages, promoting equitable development, and improving human capital and infrastructure capacity to support sustainable economic growth.